Inclusion of students as key stakeholders and agents in the induction of new university teachers: Disrupting the induction status quo - Ravhuhali, Fhatuwani; Mboweni, Hlayisani; Nendauni, Lutendo (Critical Studies in Teaching and Learning, 2023)
Ample research exists on the induction of new academics (NAs) or new university teachers (NUTs), but scholars are silent on students’ inclusion in such inductions. It is on this basis that this paper prompted the views of NAs on the inclusion of students in the induction of new academics. As academic development practitioners, who are part of the New Academics’ Transitioning into Higher Education Project (NATHEP) from 2019 and 2022, we submit and argue that the inclusion of students as partners in the induction of NAs empowers students to take ownership of their learning as students and affords them an opportunity to amplify their voices and contribute meaningfully to higher education spaces. This paper, underpinned by the Theory of Human Care and the Ethics of Care Theory, adopted a qualitative research approach in which both exploratory and explanatory research designs were triangulated. Utilising thematic data analysis, the findings of this paper were drawn from the induction questionnaires distributed and collected from NAs during induction. This paper found that the inclusion of students during induction provides NAs with an opportunity to interact with students and understand students’ challenges and expectations regarding critical teaching and learning issues. This paper has implications for both AD practitioners and higher education institutions on how the inclusion of students should be understood concerning professional development initiatives such as the induction of NAs.